Microsoft Azure for ASP.NET Core. (Packt Publishing, 2022)
Learn all about Microsoft Azure from scratch and understand how to integrate Azure into your .NET configuration About This Video Tour Microsoft Azure portal along with resource management, and build and deploy the Azure function app Set up continuous deployment with GitHub actions and Azure web services Look at unique applications to demonstrate how integrations work between our code and Microsoft Azure APIs In Detail Microsoft Azure is the premier cloud hosting platform for .NET applications. The modern .NET developer must be comfortable in navigating the different services and features and taking advantage of the cloud hosting platform to produce top-notch enterprise applications. This course will start with basic knowledge of Microsoft Azure, followed by navigating and customizing the Azure portal. After this, we will look at provisioning and managing Microsoft Azure services along with virtual machines on Azure. Next, we will provision and use Azure app services; use Azure SQL and understand the different hosting models, and use Azure Blob storage. You will also work with NoSQL databases (for example, Azure CosmosDB), monitor web applications for performance and potential errors using application insights, and scale applications and databases based on load. Then, you will set up continuous deployment with GitHub actions and Azure web app services. You will also look at how to manage application secrets in .NET applications and use Azure Service Bus and queues. Next, you will build and deploy Azure functions. Finally, you will integrate advanced .NET application security with Azure AD and Azure AD B2C. By the end of this course, you should have a fundamental understanding of what Microsoft Azure is and how its many services and third-party tools can be used to best serve your context. Audience This course is best suited for developers wanting an understanding of Microsoft Azure and wanting to know how to integrate with Azure via code. You need some C#/.NET Core knowledge and an Azure account (or free trial account) to get along with this course. Some database knowledge is required but not mandatory. Having a foundation in ASP.NET Core development will come as a plus because we will be focusing less on the fundamentals.